2007
DOI: 10.1186/1471-5945-7-4
|View full text |Cite
|
Sign up to set email alerts
|

Self reported skin morbidity and ethnicity: a population-based study in a Western community

Abstract: Background: Recent studies have shown ethnic differences concerning cardio-vascular disease, diabetes and mental health. Little is known about ethnic differences in skin morbidity. The purpose of this study was to describe possible ethnic differences in self-reported skin morbidity in a Western urban community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…Because pruritus is a symptom associated with many medical conditions, and because not everyone with chronic pmritus may present the symptom to a physician, the need for populationbased studies estimating the prevalence of the symptom becomes apparent. Compared with other large-scale studies measuring prurigo and allied conditions (14), acute pruritus within the last week ( 15,16), or undefined chronic pruritus within the past 2 years (17), the estimates arrived at in this study are higher. Chronic pruritus requires pruritus to be present for a minimum of 6 weeks (11), hence one could argue that the point, 12-month and lifetime prevalence of chronic pruritus should be lower compared with, for instance, acute pruritus within the last week assuming the study populations are otherwise comparable.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Because pruritus is a symptom associated with many medical conditions, and because not everyone with chronic pmritus may present the symptom to a physician, the need for populationbased studies estimating the prevalence of the symptom becomes apparent. Compared with other large-scale studies measuring prurigo and allied conditions (14), acute pruritus within the last week ( 15,16), or undefined chronic pruritus within the past 2 years (17), the estimates arrived at in this study are higher. Chronic pruritus requires pruritus to be present for a minimum of 6 weeks (11), hence one could argue that the point, 12-month and lifetime prevalence of chronic pruritus should be lower compared with, for instance, acute pruritus within the last week assuming the study populations are otherwise comparable.…”
Section: Discussionmentioning
confidence: 50%
“…Direct comparisons with other studies are not possible, since the effect of residential category was not addressed previously. Dalgard et al (15,16) and Rea et al (14) studied urban samples. Analyses stratified by living area were not reported by Wolkenstein et al (17).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, many studies have utilized self-administered questionnaires as well as self-report diagnosis to determine acne prevalence in their study population [8,14,15,16,17]. The few studies that have looked at this problem have concluded that generally there is poor or low agreement between self-report and trained observer acne evaluations [8, 16, 18].…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, no longitudinal study on the occurrence of chronic pruritus and its risk factors has been conducted to date. So far, cross-sectional data on sociodemographic factors have failed to show a consistent pattern of associations (4,6,7), while studies examining other associations (e.g. psychosocial) usually look at a limited number of variables simultaneously (8)(9)(10)(11) or at associations in discrete patient samples (12)(13)(14).…”
mentioning
confidence: 96%